CSF/plasma levels, transthyretin stabilisation and safety of multiple doses of tolcapone in subjects with hereditary ATTR amyloidosis - Takahashi, Yusuke; Ohashi, Nobuhiko; Takasone, Ken; Yoshinaga, Tsuneaki; Yazaki, Masahide; Roberts, Michael; Glidden, Paul F.; Sekijima, Yoshiki (Amyloid, 2022)
To investigate the effect of tolcapone on cerebrospinal fluid (CSF) transthyretin (TTR) tetramer stability in patients with hereditary transthyretin (ATTRv) amyloidosis. A total of 9 patients were enrolled in the study (3 men, 50.3 ± 14.4 years old). Three patients had central nervous system (CNS) involvement. Patients were assigned to receive tolcapone 300 mg/day or 600 mg/day for 7 days. Plasma and CSF were collected at baseline and 2 h after the final tolcapone dose. The mean CSF tolcapone and 3-O-Methyltolcapone (3-OMT) concentration were 39.4 ± 36.3 ng/mL and 26.0 ± 4.9 ng/mL, respectively, after 7 days of tolcapone dosing. Tolcapone and 3-OMT were detected in the CSF of patients with or without CNS symptoms. The mean total study drug (tolcapone + 3-OMT) to TTR molar ratio in CSF was 1.15 ± 0.59. Orally administered tolcapone significantly increased CSF TTR concentration and decreased monomer content under semi-denaturing conditions. Eight adverse events (AEs) were reported in 6 patients. All AEs were mild in severity and resolved. Tolcapone was able to cross the blood brain-barrier, highlighting its potential to decrease CNS manifestations of ATTRv amyloidosis. Tolcapone was well tolerated by patients with ATTRv amyloidosis.